Keanekaragaman vegetasi di kawasan hutan mangrove Desa Mojo, Kecamatan Ulujami, Kabupaten Pemalang, Jawa Tengah - Fajar Kartika, Aisyah; Fikriyya, Nabela; Nurul Zulkarnaen, Rizmoon (Innovation Centre for Tropical Sciences, 2024)
Mangrove forests are vital for coastal protection, biodiversity, and local livelihoods but face significant threats such as erosion, land-use changes, sedimentation, and waste pollution. This study assessed the diversity, dominance, and evenness of the mangrove ecosystem in Mojo Village, Ulujami District, Pemalang Regency, an area impacted by coastal abrasion. The research, conducted from August to September 2023, used purposive sampling with quadrant transects at four stations. Three plot sizes (10 m × 10 m, 5 m × 5 m, and 2 m × 2 m) were employed to analyze different mangrove growth stages (tree, sapling, and seedling). The mangrove diversity index ranged from 0 to 1.232, with the highest value observed in the tree stage (1.232) and the lowest in the seedling stage (0). The species Avicennia alba exhibited the highest dominance across all stages. The evenness index varied between 0 and 0.95209, indicating high evenness in trees and saplings, while the seedling stage exhibited low evenness. Water quality parameters were found to be supportive of mangrove growth. They included temperature (28.8–30.5°C), salinity (25–30 ppt), pH (5.90–6.21), and dissolved oxygen (5.5–14.9 mg/l). The results highlighted variations in diversity and evenness across the mangrove ecosystem's growth stages. The findings provide valuable insights into the current state of mangroves in the area and underscore the urgent need for continued monitoring and sustainable management to restore and conserve the mangrove forests in Mojo Village. Keywords: mangrove vegetation diversity, Mojo village, Ulujami